Builder's Competency Improvement About Simple Earthquake Resistant Houses in Blang Pulo Village, Lhokseumawe City - Sofyan; Ahmad Nayan; David Sarana; Jordan; Rahmad (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
The Indonesian region has a very high seismic intensity. Its geographic location is on three active tectonic plates, namely Indo Australia, Eurasia and the Pacific and is part of the circum Pacific belt, a series of volcanoes (ring of fire) that reaches 40,000 km in length, causing Indonesia to be frequently hit by tectonic earthquakes and volcanic eruptions. . Incident after incident seemed to alternately hit various regions in Indonesia. An earthquake with a magnitude of 9.1 on the Richter scale followed by a tsunami wave devastated the Aceh region in 2004. Another major earthquake occurred in Jokjakarta in 2006, which was followed by dozens of earthquakes in various regions in Indonesia. The most recent event was an earthquake with a magnitude of 6, 6 on the Richter scale in Banten on January 14 2022 which is reported to have damaged more than 3000 buildings. Simple houses are the group of buildings that most often experience collapse, heavy damage and minor damage. This community service activity will try to improve the ability of builders in five villages around the Malikussaleh University campus on simple earthquake-resistant housing technology. Efforts to increase these competencies will be carried out through theoretical explanations using examples and drawings, which will then be followed up with direct practice of making key components that have a major influence on the ability of buildings to withstand earthquake loads.